Sistem Pakar Identifikasi Penyakit Tanaman Cabai Rawit Menggunakan Metode Forward Chaining Berbasis Web - Siti Andriani (J-INTECH ( Journal of Information and Technology), 2020)
The loss of farmers in the cultivation of chili pepper plants is still an obstacle, because there are still many farmers who do not know the symptoms of the chili pepper plant. With this expert system, farmers are able to identify chili pepper plant disease early using a web-based forward chaining method. Recognized by looking at the symptoms that arise and the handling of chili pepper plant disease. The identification of the expert system of chili pepper plants has an accuracy value of 94.444% and an error value of 5.556% to be tested on 19 farmers and extension workers. And it can be concluded that the expert system is quite feasible to be used by farmers in early identification of chili pepper plant disease.